Гольмґард: де правили руські князі Святослав Ігоревич, Володимир Святославич та Ярослав Володимирович? - Войтович, Л.В. (Український історичний журнал, 2015)
У результаті довголітніх археологічних досліджень в основному було підтверджено,
що до середини ХІ ст. в Новгороді Великому не існувало дитинця та укріпленого
окольного граду, а новгородські «кінці» були окремими неуфортифікованими
селищами. За скандинавськими джерелами, перші «новгородські» князі
перебували в Гольмґарді. Де було це місце: на Рюриковому Городищі, новгородському
Славні, у Новгороді на Лузі чи деінде? Нижче здійснюється спроба локалізації
Гольмґарда за писемними, археологічними джерелами, аналіз часу та обставин його виникнення й занепаду. Longstanding archaeological researches mainly have confirmed that to the middle of
the 11th century, dytynets’ or fortified yard didn’t exist in Veliky Novgorod (the Great).
And non fortified separated villages near Novgorod called “kintsi” (“ends”), which appeared
in the 10th century. From Scandinavian sources it is known about more than
hundred is mentioned that duke Novgorod’s rulers lived in Holmgard. Where was this
city located: in the Rurik’s settlement, in Slavna by Novgorod, in Novgorod by Lug or
in a different settlement? The article makes an attempt to localize Holmgard on the
base writing and archaeological sources. The author analyzes time and circumstances
of Holmgard’s emergence and decline to find out the place o f it location.